Penerapan Strategi IMC Dalam Mengoptimalkan Peran Bank Syariah Indonesia Sebagai Bank Emas - Aryo Alamsyah; Satibi Satibi; Sri Maulida Agustina; Arfiani Yulianti (Jurnal Ekonomi dan Bisnis Digital, 2025)
Bank Syariah Indonesia (BSI), one of the largest Islamic banks in Indonesia, has launched Bank Emas, a gold-related investment product available at your fingertips through Byond by BSI mobile banking. The purpose of this study is to analyze BSI's implementation of Integrated Marketing Communication (IMC). The method used in this study is a literature review study with a descriptive qualitative data approach. The results show that BSI has optimally implemented the IMC Strategy to all its employees to create brand awareness among the general public.